Phonics Reading Method to Overcome Beginning Reading Difficulties on Elementary School Student in Surabaya - Faradiba Permatahati; Niken Titi Pratitis (Jurnal Multidisiplin Madani, 2024)
Reading is an important skill for students when learning activities at school because they have to understand concepts and theories from reading activities. One of the problems about beginning reading difficulties was experienced by MNE, an 8 years old grade 1 elementary school student. MNE has difficulty in reading at first, the client still finds it difficult to distinguish between letters or pronounces letter incorrectly, one of which is the letter b which reads p, g which reads j, f which reads v. MNE still don't know several letters such as the letters w, y, x, and q. The method used in this research is a qualitative approach with a case study method to strengthen the diagnosis of MNE based on existing symptoms. The assessments used were observation, interview, intelligence test, and EGRA reading ability test. The intervention using the phonic reading method for 4 sessions in 10 days. The results of the intervention showed an increase in the client’s reading ability to recognize letters well. Client’s motivation to read also increases by trying to read all things that he sees with validation from the people around him